Comparison of various surgical incisions in parotidectomy: A systematic review and network meta-analysis - Yin, Siyue; Han, Yanxun; Liu, Yuchen; Chen, Bangjie; Fu, Ziyue; Sheng, Shuyan; Wang, Jianpeng; Shen, Chuanlu; Wang, Xinyi; Jia, Yiwen (Frontiers in Oncology, 2022)
Background: This network meta-analysis aimed to comprehensively compare the operative and postoperative outcomes of different parotidectomy incisions. Methods: Embase, PubMed, Web of Science, and Cochrane Central Register of Controlled Trials were searched up to April 2022. A complete Bayesian network meta-analysis was performed using the Markov Monte Carlo method in OpenBUGS. Results: Eighteen studies with 1677 patients were included. Fourteen were retrospective cohort studies, three were prospective cohort studies, and one was a randomized controlled study. The quality of evidence was rated as very low in most comparisons. The incision satisfaction score of the V-shaped incision (VI) was higher than that of the modified Blair incision (MBI) (mean difference [MD] -2.47; 95% credible interval [CrI] -4.51, -0.43); the tumor size treated by VI was smaller than that by MBI (MD 5.15; 95% CrI 0.76, 9.38) and modified facelift incision (MFI) (MD 5.16; 95% CrI 0.34, 9.86); and the risk of transient facial palsy in the MFI was lower than that in the MBI (OR 1.92; 95% CrI 1.22, 2.94). There were no differences in operation time, drainage volume, wound infection, hematoma, salivary complications, Frey syndrome, or permanent facial palsy between incision types. Conclusion: The traditional MBI is frequently used for large tumor volumes, but the incision satisfaction score is low and postoperative complication control is poor. However, emerging incisions performed well in terms of incision satisfaction scores and control of complications. More randomized controlled trials are needed to compare the different parotidectomy incisions. Patients should be fully informed about the characteristics of each incision to make the most informed decision, along with the physician's advice.